2011
DOI: 10.1021/ma200256v
|View full text |Cite
|
Sign up to set email alerts
|

Novel, Fully Biobased Semicrystalline Polyamides

Abstract: Novel, semicrystalline polyamides and co(polyamides) were synthesized from biobased sebacic acid (SA), 2,5-diamino-2,5-dideoxy-1,4;3,6-dianhydroiditol (diaminoisoidide, DAII) as well as from 1,4-diaminobutane (DAB), also known as putrescine in nature. Low molecular weight polyamides were obtained by melt polycondensation of the salts based on these monomers or by interfacial polycondensation. In order to increase their molecular weights the polyamide prepolymers were submitted to a solid state polymerization (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
153
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(168 citation statements)
references
References 46 publications
12
153
0
3
Order By: Relevance
“…The peak positions of the fitting procedure and the spacings as calculated by Bragg's law are reported in Table 3. Within the experimental inaccuracy, the spacings do not show any significant differences according to the literature for PAs [18,19,24,40]. The amorphous regions are reflected on the smectic peak at 2h between 18°and 20°and the amorphous halo at ca.…”
Section: Crystalline Structure (Waxd)mentioning
confidence: 54%
See 2 more Smart Citations
“…The peak positions of the fitting procedure and the spacings as calculated by Bragg's law are reported in Table 3. Within the experimental inaccuracy, the spacings do not show any significant differences according to the literature for PAs [18,19,24,40]. The amorphous regions are reflected on the smectic peak at 2h between 18°and 20°and the amorphous halo at ca.…”
Section: Crystalline Structure (Waxd)mentioning
confidence: 54%
“…Jasińska et al [24] found similar results for polyamide 4.10 and its copolymers, and they described the peak at 2h = 23°as characteristic of the c-crystalline phase. On the contrary, for PA 6.6, Liu and coworkers assign this reflection as one of the distinctive features of the a-phase in polyamides and state that polyamides present usually more stable a-phase rather than c ones in XRD [20].…”
Section: Crystalline Structure (Waxd)mentioning
confidence: 57%
See 1 more Smart Citation
“…In recent years, many different sustainable biobased polyamides have been described, for example, those derived from sebacic acid [89] or succinic acid, [90] which would give enough material for as eparate review.I n terms of terpene-based polyamides, it was shown some time ago that 6 could be transformed into its oxime and then into the corresponding lactam, which has been used for af ew homo-a nd copolymerization studies by ROP. [91,92] For homopolymers, intrinsic viscosity, IR absorption, and optical activity was determined for characterization, but no molecular weights could be given.L ater,i tw as shown that as econd regioisomeric lactam derived from 6 could also be isolated.…”
Section: Rop Of Terpene-basedlactams To Polyamidesmentioning
confidence: 99%
“…However, odd derivatives are gaining interest due to the development of materials based on renewable resources because of concerns over long-term availability of chemicals derived from fossil resources [1,2]. Nylons 5 6 [3-6], 6 9 [7] and 13 6 [8] can be considered in this context.…”
Section: Introductionmentioning
confidence: 99%